Complex Analyses of Short Inverted Repeats in All Sequenced Chloroplast DNAs - Brázda, Václav; Lýsek, Jiří; Bartas, Martin; Fojta, Miroslav (BioMed research international, 2018)
Chloroplasts are key organelles in the management of oxygen in algae and plants and are therefore crucial for all living beings that consume oxygen. Chloroplasts typically contain a circular DNA molecule with nucleus-independent replication and heredity. Using "palindrome analyser" we performed complete analyses of short inverted repeats (S-IRs) in all chloroplast DNAs (cpDNAs) available from the NCBI genome database. Our results provide basic parameters of cpDNAs including comparative information on localization, frequency, and differences in S-IR presence. In a total of 2,565 cpDNA sequences available, the average frequency of S-IRs in cpDNA genomes is 45 S-IRs/per kbp, significantly higher than that found in mitochondrial DNA sequences. The frequency of S-IRs in cpDNAs generally decreased with S-IR length, but not for S-IRs 15, 22, 24, or 27 bp long, which are significantly more abundant than S-IRs with other lengths. These results point to the importance of specific S-IRs in cpDNA genomes. Moreover, comparison by Levenshtein distance of S-IR similarities showed that a limited number of S-IR sequences are shared in the majority of cpDNAs. S-IRs are not located randomly in cpDNAs, but are length-dependently enriched in specific locations, including the repeat region, stem, introns, and tRNA regions. The highest enrichment was found for 12 bp and longer S-IRs in the stem-loop region followed by 12 bp and longer S-IRs located before the repeat region. On the other hand, S-IRs are relatively rare in rRNA sequences and around introns. These data show nonrandom and conserved arrangements of S-IRs in chloroplast genomes.
Keywords: Evolution, Molecular; obrácené repetice; Introns; fylogeneze; Inverted Repeat Sequences; DNA, Chloroplast; chloroplasty; introny; genom chloroplastový; DNA chloroplastová; Genome, Chloroplast; Phylogeny; Chloroplasts; molekulární evoluce